Analysis of Sleeve Dipole Antennas Fed by Ferrite-Loaded Coaxial Cables for a Scaled-Down Cross-Borehole Radar - Jung, Ji-Hyun; Cho, Jae-Hyoung; Kim, Se-Yun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
Two equivalent models to sleeve dipole antennas fed by ferrite-loaded coaxial cables for a scaled-down cross-borehole radar are tested by employing the finite-difference time-domain method. Compared to the measured diffraction patterns of an air-filled circular cylinder in water, the simulated results based on the simplified perfect magnetic conductor model cannot provide sufficient attenuation not only in the single dip pattern at 2.6 GHz but also in double dip pattern at 2.8 GHz. It leads us to develop a more accurate one so-called distributed element model which is implemented by a finite sum of serial sections consisting of a resistor, a finite length of perfect electric conductor (PEC) cylinder, an inductor, and the same PEC cylinder. When the values of the distributed elements as well as the number of serial sections are adjusted properly, the simulated diffraction patterns closely approach to the experimentally measured data at both frequencies of 2.6 and 2.8 GHz.
Keywords: MAGNETIZED FERRITES; FDTD ANALYSIS; PROPAGATION; PATTERN; MEDIA; MODEL; WAVE